2021
DOI: 10.2174/1570163817666200712171652
|View full text |Cite
|
Sign up to set email alerts
|

Potential Fatty Acid as Antibacterial Agent Against Oral Bacteria of Streptococcus mutans and Streptococcus sanguinis from Basil (Ocimum americanum): In vitro and In silico Studies

Abstract: Background: Streptococcus mutans and Streptococcus sanguinis are Gram-positive bacteria that cause dental caries. The MurA enzyme is a catalyst in the formation of peptidoglycan in the bacterial cell wall making it ideal as an antibacterial target. Basil (Ocimum americanum) is an edible plant medicine that diverse, very widely spreading, used as herbal for a long time, and it was reported to have pharmacology effect as antibacterial activity. The purpose of this study is to identify antibacterial compounds fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Meric and colleagues reported similar frequencies of S. mutans, and S. sanguinis among caries and caries free groups of subjects ( Meriç et al, 2020 ). Furthermore, S. sanguinis was reported for the pathogenesis of caries ( Herdiyati et al, 2021 , Kurnia et al, 2020 ), and infective endocarditis ( Martini et al, 2020 ). In the present study, S. mutans was not identified in any of the 40 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Meric and colleagues reported similar frequencies of S. mutans, and S. sanguinis among caries and caries free groups of subjects ( Meriç et al, 2020 ). Furthermore, S. sanguinis was reported for the pathogenesis of caries ( Herdiyati et al, 2021 , Kurnia et al, 2020 ), and infective endocarditis ( Martini et al, 2020 ). In the present study, S. mutans was not identified in any of the 40 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophilic interactions, such as hydrogen bonds, play an important role in determining binding affinity value and affect the stability of ligand-protein complexes owing to stronger interactions. 34 , 35 …”
Section: Discussionmentioning
confidence: 99%
“…Hydrophilic interactions, such as hydrogen bonds, play an important role in determining binding affinity value and affect the stability of ligandprotein complexes owing to stronger interactions. 34,35 In experiments on ligand-ER-α complex formation, compound 2 had the highest binding affinity, suggesting efficient occupation of the active ER-α pocket. Compound 2 displayed more hydrophilic bonds (Glu353, Gly521, His524, Phe404, Ala350, Leu387, Leu391, Leu525) relative to compound 1 and tamoxifen.…”
Section: Discussionmentioning
confidence: 99%
“…and other non-QS targets (proteins involved in efflux pumps, oxidative stress, and ergosterol synthesis) make FAs a new paradigm to cope with drug-resistant bacteria (Kumar et al, 2020). Of these, medium-chain fatty acids (MCFAs) and their monoglycerides have a broad spectrum of microbicidal activity against a wide range of pathogens both in vitro and in vivo, including multidrug-resistant bacteria, enveloped viruses, algae, fungi, and protozoa (Bergsson et al, 2001;Hilmarsson et al, 2007;Yoon et al, 2018;Zhou et al, 2019;Heriyati et al, 2020;Welch et al, 2020).…”
Section: Antimicrobial Effect Of the Lauric Acid And Monolaurinmentioning
confidence: 99%
“…Furthermore, MCFAs can directly inhibit membrane enzymes such as glucosyltransferase and also target other membrane-associated proteins (Yoon et al, 2018). In some in silico studies, LA has been proposed as a natural antibacterial agent via inhibiting the MurA enzyme, which is involved in bacterial cell wall biosynthesis (Heriyati et al, 2020). Galbraith and Miller (1973a,b) reported that the activity of LA was decreased by Mg 2+ and Ca 2+ ions and increased by lower pH, suggesting that the uptake of LA is modulated by physico-chemical properties of both the acid and the bacterial surface.…”
Section: Antimicrobial Effect Of the Lauric Acid And Monolaurinmentioning
confidence: 99%